AIAA Guidance, Navigation, and Control Conference and Exhibit 2006
DOI: 10.2514/6.2006-6320
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Aircraft Landings Under Constrained Position Shifting

Abstract: Optimal scheduling of airport runway operations can play an important role in improving the safety and efficiency of the National Airspace System (NAS). Methods that compute the optimal landing sequence and landing times of aircraft must accommodate practical issues that affect the implementation of the schedule. One such practical consideration, known as Constrained Position Shifting (CPS), is the restriction that each aircraft must land within a pre-specified number of positions of its place in the First-Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 9 publications
0
111
0
Order By: Relevance
“…In prior work, it has been shown that every feasible k-CPS sequence can be represented as a path in a directed graph whose size is polynomially bounded in n and k [16]. This enables us to solve the problem at hand using dynamic programming, as is demonstrated in this section.…”
Section: Algorithmmentioning
confidence: 94%
See 4 more Smart Citations
“…In prior work, it has been shown that every feasible k-CPS sequence can be represented as a path in a directed graph whose size is polynomially bounded in n and k [16]. This enables us to solve the problem at hand using dynamic programming, as is demonstrated in this section.…”
Section: Algorithmmentioning
confidence: 94%
“…The maximum number of position shifts allowed is denoted by k (k 3 for most runway systems), and the resulting environment is referred to as a k-CPS scenario. The restricted deviation from the FCFS order helps maintain equity among aircraft operators and also increases the predictability of landing times [16].…”
Section: ) Limited Deviation From Fcfsmentioning
confidence: 99%
See 3 more Smart Citations